Ibn Sina's Perspective Education Concept And Its Relevance To The Independent Learning Curriculum - Putri, Musdalipah; Haikal As-Shidqi, Muhammad (Gunung Djati Conference Series, 2025)
Education is a defense premise that has the goal of developing values and skills in students. Education, according to Ibn Sina, focuses more on formal learning and independent learning. This makes the author think that Ibn Sina's perspective is still valid and can be taken.The research method used is library research by (1) modifying the problem, (2) looking for related articles, (3) sorting out information and (4) analyzing the data obtained. The result of this study is that Ibn Sina's perspective education is motivated by his philosophical thoughts. So that the purpose of Education from Ibn Sina's perspective prioritizes the application to the soul of the students. The educational methods used by Ibn Sina are: Discussion method, talqin method, demonstration method, habituation and example method, internship method, assignment method, targhib and tarhib method. So that in this Ibn Sina education a teacher must be able to take his attention, be able to take his heart. The relevance to the independent curriculum is in the same goal, namely: Students with noble character and high insight display superior and competitive quality of human resources. And the methodology of Ibn Sina's education is very relevant to the development of the current independent curriculum.